Going up and down: Rethinking the empirics of growth in the developing and newly industrialized world - Francesco Lamperti; Clara Elisabetta Mattei (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
Growth dynamics are remarkably heterogeneous, in particular when one focuses on developing countries. Economic miracles and failures are embedded within extended phases of either growth or decline. We propose a methodology and a taxonomy that will characterize countries' growth patterns on the basis of the sequence of regimes they experience. In particular, we emphasize the difference between expansionary and recessionary regimes and, after classifying the growth pattern of all 123 developing countries in our dataset, we explore cross-sectional empirical regularities which emerge during upward and downward growth phases. Results show that expansionary regimes are associated with convergence and positive correlation between growth and (short run) volatility. On the contrary, in recessionary regimes, poorer countries face deeper failures and a negative correlation between growth and volatility is found, signifying that output fluctuates less around the trend during strong rather than mild recessions. Finally, we discover that regimes of growth and recession show similar average length (about 16 years). Although recessions on average are remarkably pronounced (14% loss), during expansions the magnitude of growth is much larger.
Keywords: O11; O40; O47; 330; growth; structural breaks; expansionary and recessionary regimes; convergence